Identification of Vectors of Plasmodium knowlesi and Other Malaria Parasites in Sarawak - Ang, Joshua Xin De (Universiti Malaysia Sarawak (UNIMAS), 2021)
The vectors for Plasmodium knowlesi, a significant cause of human malaria in Southeast Asia, identified previously in nature all belong to the Anopheles Leucosphyrus Group. Only one study has been previously undertaken in Sarawak, Malaysian Borneo, to identify vectors of P. knowlesi, where Anopheles latens was incriminated as the vector in Kapit, central Sarawak. A study was therefore undertaken to identify malaria vectors in the Betong Division and Lawas District in Sarawak. A total of 2,287 mosquitoes were collected from Betong and Lawas in the duration of this study. Using the simian malaria parasite species- specific PCR assays, five An. barbirostris, two An. collessi, three An. roperi, which do not belong to the Leucosphyrus Group and nine An. balabacensis, five An. latens which are members of the Leucosphyrus Group were shown to harbour at least one of the five simian malaria parasites tested. Three of these An. roperi and one An. collessi were collected before 0900 hr. On the other hand, P. knowlesi DNA was also detected in the head and thorax of Culex spp. and the salivary glands of Armigeres spp.; Culex spp. therefore could not be confirmed as a vector as the evidence is insufficient to prove its role in the transmission of P. knowlesi. The ML and NJ trees constructed with a total of 108 plasmodial SSUrDNA isolated from mosquitoes showed that An. barbirostris and Armigeres spp. were only susceptible to P. knowlesi while the other vectors were infected with a variety of both identifiable and unidentifiable parasites. Plasmodium coatneyi was found only in An. roperi while P. cynomolgi was detected in the salivary glands of two members of the Leucosphyrus Group; An. balabacensis and An. latens. Parasites closely related to P. simiovale, is found in Betong to be transmitted by An. collessi, An. roperi, and An. latens. Phylogenetic analyses of the SSUrRNA gene have uncovered a large number of unidentified parasites which appeared to be closely related to P. hylobati and P. inui. When these unidentified sequences iv were aligned to a wide range of parasitic protozoans found in different hosts, they still clustered around the simian malaria parasites, suggesting that these parasites originated from simian hosts. In terms of the identity of vectors, the size of the ITS2 region of An. barbirostris from this study and the phylogenetic trees constructed using the region suggest that the An. barbirostris collected in the current study and those from a separate study in Selangor are probably the same species of mosquito but formed a distinct clade, which we have termed Clade VI. ML and NJ trees constructed with the CO1 gene showed that An. barbirostris Clade VI is significantly distinct from the other members of the Barbirostris Group from Thailand and Indonesia. Phylogenetic analyses of the CO1 gene of morphologically identified An. balabacensis from Lawas have shown that they formed a clade with the same species from Sabah and South Kalimantan while An. latens from Betong have separated into two distinct clades. Three of the An. latens formed a clade with An. introlatus and An. nemophilous while the other three formed a distinct clade. Incidentally, the ones which clustered with An. introlatus and An. nemophilous were shown by PCR and sequencing results to have multiple malaria parasite infections while those that formed a clade by themselves were only infected by P. knowlesi. The overall findings of the current study show that vectors of P. knowlesi and other simian malaria parasites are not restricted only to the Leucosphyrus Group. Further intensive studies of the bionomics of each of these novel vectors will be crucial to inform the implementation of efficient vector control methods.